Transformasi Kurikulum Pendidikan Islam Abad Ke-21: Tantangan Digital, Integrasi Keilmuan, dan Strategi Manajerial Berbasis Nilai - Nurarifah; Ramlis Harman Susanto; Abhanda Amra (Indo-MathEdu Intellectuals Journal, 2026)
Social change, globalization, and the development of artificial intelligence pose challenges in the form of suboptimal integration between mastery of 21st-century competencies and strengthening ethical and spiritual values ​​in the Islamic education curriculum. This article aims to analyze the challenges of the 21st-century Islamic education curriculum and formulate a curriculum transformation strategy from an Islamic education management perspective. This study uses a qualitative approach with library research. Data sources were obtained from madrasah curriculum regulations, national and international journal articles published between 2019 and 2025, and classical Islamic education literature relevant to curriculum development and Islamic education management. Data collection techniques were carried out through literature searches, selection, and classification based on the relevance of the research theme. Data were analyzed using content analysis techniques through the stages of data reduction, theme categorization, concept interpretation, and theoretical synthesis. The results of the study indicate that the main challenges to the Islamic education curriculum include technological and AI disruption, globalization of values, changes in student character, teacher readiness, and the digital infrastructure gap. This article offers a curriculum transformation strategy through scientific integration-interconnection, Islamization of 4C competencies, ethical digital literacy, authentic assessment, and data-based curriculum leadership.